How sagittal alignment changes can affect independent horizontal gaze after neuromuscular scoliosis correction - Kim, Sung Taeck; Kim, Hyoungmin; Chang, Bong-Soon; Jang, Seonpyo; Lee, Junyeop; Chang, Sam Yeol (Journal of orthopaedic surgery and research, 2025)
Background When surgical correction for spinal deformity is performed for neuromuscular scoliosis (NMS) patients, sudden changes in sagittal spinal alignment after surgery can cause difficulties in maintaining independent horizontal gaze. Typically, patients with weak neck flexors can experience a loss of head control during neck extension that cannot be restored to a neutral position to allow horizontal gaze. This study aimed to analyze the radiological factors associated with the ability to maintain an independent horizontal gaze following deformity correction surgery in patients with NMS. Materials and methods Patients who underwent deformity correction surgery for the NMS from 2013 to 2023 were included. We assessed whether the patient could maintain a horizontal gaze without a headrest after deformity correction. Clinical demographics and radiographic alignment parameters before and after surgery were collected. Multivariable logistic regression was performed to identify risk factors of postoperative loss of head control. Results 88 NMS patients were included in this study. After deformity correction, 31 (35%) patients could not maintain a horizontal gaze without a headrest at postoperative 3 months. The group of patients who maintained horizontal gaze had a significantly greater postoperative chin-brow vertical angle (4.3°±-10.6 vs. -4.7°±11.6, p = 0.003) and C7-S1 sagittal vertical axis (67.0 mm ± 46.5 vs. 29.3 mm ± 40.1, p = 0.002) than the group who could not. Logistic regression analysis showed that a greater increase of lumbar lordosis (odds ratio = 1.018, p = 0.039) and change in C7-S1 sagittal vertical axis (odds ratio = 1.020, p = 0.025) were associated with an inability to maintain horizontal gaze. Conclusions In this study, the loss of ability to maintain independent horizontal gaze after deformity correction for NMS was associated with a greater increase in lumbar lordosis. Maintaining preoperative sagittal balance is crucial for head control in patients undergoing deformity correction for NMS.